San Benito y Europa - Padrón, Héctor Jorge (2001)
The author analyses the reasons why Saint Benedict has been called “Father of Europe". In thls sense, Saint Benedict, Father of the western monasticism and therefore of Europe, teaches us how to embrace the totality of virtues in our own historical experience, just for discovering that non only the human being, but also the world and the history, are built from the inner. So Europe. proud of its history and its conquests, should leam back again that Benedictine peace is the dimensión from where the human dignity can be recovered.